MINIMALLY INVASIVE THORACOSCOPIC SURGERY AS A DIAGNOSTIC AND THERAPEUTIC APPROACH IN BILATERAL PNEUMOTHORAX IN PREGNANCY CAUSED BY LYMPHANGIOLEIOMYOMATOSIS – A CASE REPORT - Garabinović, Željko; Čolić, Nikola; Vasić Madžarević, Jelena; Savić, Milan (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Lymphangioleiomyomatosis (LAM) is a rare disease which mainly occurs in women in the generative period, as well as during pregnancy, while only a few individual cases have been described in men. It occurs in sporadic form or is associated with tuberous sclerosis complex. The diagnosis can be made on the basis of high-resolution computed tomography (HRCT) findings, or histopathological analysis is required. Clinical manifestations of the disease include the following: progressive dyspnea on exertion, recurrent pneumothorax, chylothorax, angiomyolipomas and lymphangiomyomas. Case report: A 32-year-old female patient was admitted to our clinic, in her third trimester of pregnancy, after a left-sided pneumothorax was verified on chest X-ray. Initial treatment included needle aspiration, followed by thoracic drainage of the left pleural cavity. Due to the prolonged air leak through the thoracic drain and the advanced stage of the pregnancy, a caesarean section was performed. After delivery, chest X-ray revealed complete right-sided pneumothorax, which required thoracic drainage, as well as an insufficiently reexpanded left lung. HRCT was performed and cystic bullous changes in the lungs were noted; LAM was histopathologically verified through a minimally invasive thoraco-surgical approach, first on the left and then on the right side, while bilateral pneumothorax was surgically treated. Conclusion: Pneumothorax is a common complication of LAM. Due to the high recurrence rate, definitive early surgical intervention should be performed. Current guidelines recommend chemical pleurodesis and surgery for the first pneumothorax. When treating pneumothorax in pregnancy, the appropriate therapeutic procedure should be applied, taking into account the safety of the pregnancy and of the delivery.